Evaluation of the implementation of the Back Skills Training (BeST) programme using online training: a cohort implementation study. (December 2020) - Sugavanam, Thavapriya; Williamson, Esther; Fordham, Beth; Hansen, Zara; Richmond, Helen; Hall, Amanda; Ali, Usama; Copsey, Bethan; Lamb, Sarah E.
Abstract: Objectives: 1) Evaluate implementation of the Back Skills Training (BeST) programme, a group cognitive behavioural approach for patients with low back pain (LBP) developed for a clinical trial, into the National Health Service (NHS) in the United Kingdom; 2) Compare patient outcomes with the BeST Trial results. Design: Two stage observational cohort implementation study. Participants: Stage 1: NHS Clinicians enrolled in BeST online training. Stage 2: Patients with LBP attending NHS physiotherapy departments and enrolled in the BeST programme. Intervention: An online training and implementation programme. Outcomes: Stage 1: LBP attitudes and beliefs, self-rated competence, intention and actual implementation were collected before, immediately, 4- and 12-months post-training. Stage 2: Patients rated pain, function, recovery and satisfaction before and up to one year after attending the BeST programme. Results: Stage 1: 1324 clinicians (157 NHS Trusts) enrolled in the training; 586 (44%) clinicians (101 NHS Trusts) completed training; 443/586 (76%) clinicians provided post-training data; 253/443 (57%) clinicians intended to implement the programme; 148/381 (39%) clinicians (54 NHS Trusts) provided follow-up data; 49/148 (33.1%) clinicians (27 NHS Trusts) implemented the programme. Attitudes and beliefs shifted towards a biopsychosocial model post-training. Stage 2: 923 patients were enrolled. Patients reported improvements in function (mean change: 1.55; 95%CI: 1.25, 1.86) and pain (−0.84; −1.1, −0.58) at follow-up. The majority rated themselves improved and satisfied with the programme. Conclusion: Online training had good reach into NHS Trusts although, not everyone went onto implement the programme. Improvements in function that were consistent with the original trial were demonstrated.